Misuse of antibiotics in pediatric infections: a call for parental awareness - Ikram, Hiba; Faheem, Anfaal (Journal of the Pakistan Medical Association, 2025)
Madam, Misuse of antibiotics refers to their incorrect use, including using them for non-bacterial infections, using the wrong type, incorrect dosage, or improper duration of treatment, all of which can lead to reduced effectiveness. This misuse significantly contributes to developing antimicrobial resistance (AMR), a phenomenon where bacteria adapt, rendering antibiotics ineffective. AMR is an alarming threat to global health, compromising the treatment of common infections, leading to prolonged illnesses, increased healthcare costs, and higher mortality rates.(1) WHO estimates that multidrug-resistant bacterial infections caused 700,000 deaths annually, including nearly 200,000 infants and children. Children are particularly vulnerable due to frequent antibiotic prescriptions, limited alternatives, and the widespread abuse of antibiotics.(2) Parents play a significant role in antibiotic misuse, often resorting to have self-medication their children. According to research, on average, 24% of parents reported having self-medicated their children with antibiotics or were willing to do so. Prevalence varied by country, from 1% in Greece to as high as 69% in Saudi Arabia. These findings emphasize the necessity for greater awareness and stricter regulations to prevent antibiotic misuse and combat antimicrobial resistance.(3) Parental misuse of antibiotics stems from a lack of awareness, personal beliefs, and knowledge gaps. Easy access to unregulated antibiotics, leftover medications, and healthcare barriers such as cost, distance, and transport issues worsen the problem. Many rely on advice from family, friends, and pharmacies, and some parents pressure doctors into unnecessary prescriptions.(4) Educating parents through awareness programmes is key to reducing antibiotic misuse and preventing antimicrobial resistance. A recent study assessed the impact of a antimicrobial stewardship training programme of antibiotics among family caregivers, showing promising results. knowledge and practices of family caregivers regarding antibiotic use improved, with kept 18.36 to 23.28 and 9.83 to 12.37, respectively, highlighting the effectiveness of training in fostering responsible use.(5) In low- and middle-income countries (LMICs) like Pakistan, knowledge gaps, inadequate healthcare facilities, and low literacy rates fuel self-medication and antibiotic overuse, posing serious health risks to children. Raising awareness and educating parents is crucial to tackling AMR in children. Healthcare professionals should seize the opportunity during consultations to counsel parents on the appropriate use of antibiotics. Government-backed awareness campaigns through media and community health centres can enhance awareness while enforcing strict regulations of over-the-counter antibiotic sales can promote responsible usage. Implementing these strategies can significantly reduce AMR, improve health outcomes and easing the burden on healthcare facilities.